Adverbial Markers of Epistemic Modality Across Disciplinary Discourses: A Contrastive Study of Research Articles in Six Academic Disciplines - Rozumko, Agata (Studia Anglica Posnaniensia, 2017)
Epistemic adverbs, like other markers of epistemic modality, are concerned with the speaker’s assessment of the truth value of the proposition. In other words, they indicate that the speaker considers certain situations as possible, impossible, probable, certain, or uncertain. At the same time, they signal the author’s presence in the text, and invite the reader to make his/her own conclusions and interpretations. The use of modal markers has been demonstrated to differ across academic disciplines, but the specific differences concerning the use of epistemic adverbs have not been studied systematically. This paper investigates the use of epistemic adverbs in research articles representing six disciplines belonging to three different branches of science: the humanities (linguistics and literary studies), the social sciences (law and sociology), and the natural sciences (physics and medicine), with the aim of establishing discipline-specific tendencies in their use. The study is based on a corpus of 160 research articles compiled by the author. It begins with an attempt at delimiting the category of epistemic adverbs in English. After that, a list of the most frequent epistemic adverbs in the subcorpora of all the disciplines is established and discussed. The study demonstrates that frequent use of epistemic adverbs is largely a property of research articles in the humanities and social sciences. Medical and physics research articles use them significantly less often. The most frequent epistemic adverbs in the research articles under analysis include indeed, perhaps, clearly, certainly, of course, arguably, possibly, and reportedly. Some adverbs appear to be associated with specific disciplines, e.g., clearly (physics, linguistics, sociology, medicine), indeed (linguistics, literary studies, sociology), possibly, reportedly (medicine), arguably (law). The association of individual adverbs with specific disciplines may serve as an important clue to the understanding of their functions, in particular in the case of the less frequent ones, such as arguably and reportedly, which remain significantly understudied. The findings may also prove useful in teaching English for academic purposes.